Pricing the future : finance, physics, and the 300-year journey to the Black-Scholes equation : a story of genius and discovery - Szpiro, George, 1950- (Basic Books, 2011)
Options have been traded for hundreds of years, but investment decisions were based on gut feelings until the Nobel Prize-winning discovery of the Black-Scholes options pricing model in 1973 ushered in the era of the "quants." Wall Street would never be the same. In Pricing the Future, financial economist George G. Szpiro tells the fascinating stories of the pioneers of mathematical finance who conducted the search for the elusive options pricing formula. From the broker's assistant who published the first mathematical explanation of financial markets to Albert Einstein and other scientists w.